2009
DOI: 10.1016/j.bbabio.2009.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, calcium and cell death: A deadly triad in neurodegeneration

Abstract: Mitochondrial Ca2+ accumulation is a tightly controlled process, in turn regulating functions as diverse as aerobic metabolism and induction of cell death. The link between Ca2+ (dys)regulation, mitochondria and cellular derangement is particularly evident in neurodegenerative disorders, in which genetic models and environmental factors allowed to identify common traits in the pathogenic routes. We will here summarize: i) the current view of mechanisms and functions of mitochondrial Ca2+ homeostasis, ii) the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
205
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(209 citation statements)
references
References 113 publications
1
205
0
3
Order By: Relevance
“…As expected, both of these conditions lowered cell viability in control cells, confirming the notion that sustained [Ca 2+ ] mt overload enhances cell death. 44,45 More importantly, the same manipulations cause a much higher decrease of cell viability in Pat#1 cells (Figure 6d). This indicates that the decrease of mitochondrial Ca 2+ uptake in 13514A4G fibroblasts is a pro-survival compensatory mechanism in these cells.…”
Section: Resultsmentioning
confidence: 83%
“…As expected, both of these conditions lowered cell viability in control cells, confirming the notion that sustained [Ca 2+ ] mt overload enhances cell death. 44,45 More importantly, the same manipulations cause a much higher decrease of cell viability in Pat#1 cells (Figure 6d). This indicates that the decrease of mitochondrial Ca 2+ uptake in 13514A4G fibroblasts is a pro-survival compensatory mechanism in these cells.…”
Section: Resultsmentioning
confidence: 83%
“…Previous work showed that Ca 2+ homeostasis is dysregulated in cellular models of AD, as well as in human AD brains (Berridge, Bootman & Lipp, 1998; Celsi et al., 2009; Garwood et al., 2013). Surprisingly, our data showed decreased levels of free calcium, both in mitochondria and in cytoplasm, after the addition of the Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported recently (14) that presenilins are enriched in ER mitochondriaassociated membranes, i.e., the ER membrane domains interacting closely with mitochondria and endowed with key players of the Ca 2+ -handling machinery (15). This finding, together with the generally accepted concept that mitochondrial deficits are key events in most neurodegenerative diseases (16,17), and more specifically in AD (18, 19), led us to investigate the effect of presenilins on ER-mitochondria cross-talk.By directly measuring mitochondrial Ca 2+ dynamics, we show here that PS2, but not PS1, favors Ca 2+ transfer between ER and mitochondria, an effect reduced by PS2 down-regulation and enhanced by the expression of PS2 mutants. The most striking modification associated with PS2 expression is an increased number of contact sites between ER and mitochondria.…”
mentioning
confidence: 99%
“…It has been reported recently (14) that presenilins are enriched in ER mitochondriaassociated membranes, i.e., the ER membrane domains interacting closely with mitochondria and endowed with key players of the Ca 2+ -handling machinery (15). This finding, together with the generally accepted concept that mitochondrial deficits are key events in most neurodegenerative diseases (16,17), and more specifically in AD (18, 19), led us to investigate the effect of presenilins on ER-mitochondria cross-talk.…”
mentioning
confidence: 99%